On the Diagnosis of Cyber-Physical Production Systems - State-of-the-Art and Research Agenda - Niggemann, Oliver; Lohweg, Volker (Twenty-Ninth Conference on Artificial Intelligence (AAAI-15))
Cyber-Physical Production Systems (CPPSs) are in the focus of research, industry and politics: By applying new IT and new computer science solutions, production systems will become more adaptable, more resource ef- ficient and more user friendly. The analysis and diagnosis of such systems is a major part of this trend: Plants should detect automatically wear, faults and suboptimal configurations. This paper reflects the current state-of- the-art in diagnosis against the requirements of CPPSs, identifies three main gaps and gives application scenarios to outline first ideas for potential solutions to close these gaps.
Keywords: Cyber-Physical Systems; Machine Learning; Diagnosis; Anomaly Detection